2016
DOI: 10.1016/j.psyneuen.2016.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Serum brain-derived neurotrophic factor (BDNF) across pregnancy and postpartum: Associations with race, depressive symptoms, and low birth weight

Abstract: Background Brain-derived neurotrophic factor (BDNF) is implicated as a causal factor in major depression and is critical to placental development during pregnancy. Longitudinal data on BDNF across the perinatal period are lacking. These data are of interest given the potential implications for maternal mood and fetal growth, particularly among Black women who show ~2-fold greater risk for delivering low birth weight infants. Methods Serum BDNF, serum cortisol, and depressive symptoms (per CES-D) were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 51 publications
3
67
1
Order By: Relevance
“…Mayeur et al (, ) have hypothesized that neurotrophins regulate fetoplacental development. A recent report showed that serum BDNF levels are higher in the first trimester of the pregnancy and at the postpartum stage (Christian et al, ). During pregnancy, the serum BDNF levels declined dramatically from the first to the third trimesters of pregnancy and increased considerably during the postpartum stage (Christian et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mayeur et al (, ) have hypothesized that neurotrophins regulate fetoplacental development. A recent report showed that serum BDNF levels are higher in the first trimester of the pregnancy and at the postpartum stage (Christian et al, ). During pregnancy, the serum BDNF levels declined dramatically from the first to the third trimesters of pregnancy and increased considerably during the postpartum stage (Christian et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that serum BDNF levels are higher in the first trimester of the pregnancy and at the postpartum stage (Christian et al, ). During pregnancy, the serum BDNF levels declined dramatically from the first to the third trimesters of pregnancy and increased considerably during the postpartum stage (Christian et al, ). In addition, several reports have suggested that BDNF regulated the dendritic spine formation or regression (for review see Bennett & Lagopoulos, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of additional importance is the fact that African American women are significantly more likely to show evidence of maternal stress in the context of PTB as well as pregnancy associated maternal cortisol patterns that differ significantly from white women (Christian et al, 2016; Glynn et al, 2007). As such, it is critical that studies assessing biological pathways to expedited birth be powered to examine effects among African American women.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding and use of biomarkers that reflect the pathophysiology of maternal depression remains limited. Serum brain-derived neurotrophic factor (BDNF) has been proposed as a biomarker for perinatal depression (Christian et al 2016;Gao et al 2016) (Guintivano et al 2017). BDNF is a neurotrophin involved in neuroplasticity and implicated in the pathophysiology and treatment of mood disorders (Castren et al 2007): with lower serum BDNF levels being associated with depression (aan het Rot et al 2009).…”
Section: Introductionmentioning
confidence: 99%